Journal of Food Science and Technology Nepal (JFSTN): Past, Present and Future - Dahal, Nawa Raj (Journal of Food Science and Technology Nepal, 2019)
Journal of Food Science and Technology Nepal (JFSTN) is one of the major publications of Nepal Food Scientists and Technologists (NEFOSTA). In the history of its 35 years (from 1984) of formation of NEFOSTA, JFSTN had begun to publish from twenty years (from 2005) and upto the present year of 2019; eleven issues of JFSTN (Volume 1, 2005 to Volume 11, 2019) have already been published and altogether 190 articles of different types (Review articles 39, Research papers 102, Research notes 42,view point 1 and short communication 6) from 16 different countries have been published in these eleven issues of JFSTN. This communication wishes to explore the information about the status, progress and significance as well as way forward for the publication of JFSTN with respect to the development of Food Science and Technology Sector in Nepal.